2016
DOI: 10.1007/s00395-016-0585-y
|View full text |Cite
|
Sign up to set email alerts
|

LRP5/canonical Wnt signalling and healing of ischemic myocardium

Abstract: LRP5 (low-density lipoprotein receptor-related protein 5) activates canonical Wnt signalling. LRP5 plays multiple roles including regulation of lipoprotein and cholesterol homeostasis as well as innate immunity cell function. However, it is not known whether LRP5 has a role in the myocardium. The aim of this study was to investigate LRP5 and Wnt signalling in myocardial remodelling after acute myocardial infarction (MI). Wnt protein levels were determined in a hypercholesterolemic porcine model of MI, in Lrp5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Myocardial damage, measured blindly as previously done in [16], was significantly larger in Lrp5 -/- mice than in Wt mice. However myocardial damage assessment was independent of CHIR99021 treatments and GSK3β levels.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Myocardial damage, measured blindly as previously done in [16], was significantly larger in Lrp5 -/- mice than in Wt mice. However myocardial damage assessment was independent of CHIR99021 treatments and GSK3β levels.…”
Section: Resultsmentioning
confidence: 89%
“…We have recently described the prosurvival function of the canonical Wnt pathway in vascular cells of atherosclerotic lesions [5, 1315] and in myocardial injury (MI) [16]. Expression of several Wnt pathway proteins such as β-catenin and Dvl are increased in the damaged tissue after experimental myocardial infarction-induction [1720].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, deletion of LRP5 was found to have a deleterious effect on infarct healing in mice. Moreover, human hearts explanted due to ischemic cardiomyopathy expressed higher levels of LRP5 and β -catenin compared with dilated cardiomyopathy ( Borrell-Pages et al, 2016b ). These results could be confirmed using mice carrying a cardiomyocyte-specific deletion of LRP5 and 6 ( Wo et al, 2016 ).…”
Section: Wnt Signaling In Cardiac Diseasementioning
confidence: 99%
“…Subsequent activation of the canonical Wnt-signaling pathway may protect against postischemic damage, because LRP-5 knockout mice had larger infarcts compared to wild-type mice [19]. Whether PCSK9 is involved in the myocardial effects of LRP-5 remains to be established.…”
Section: Pcsk9 Effects Distinct From Hepatic Ldlr Regulationmentioning
confidence: 99%